Formation of high-temperature inner oxide scale on low alloy steels: Segregation, partitioning and transformation reactions. (February 2022) - Zhang, Y.D.; Jin, S.B.; Jiang, C.L.; Yang, Jijin; Sha, G.
Abstract: High-temperature oxide scales on two low-alloy steels were carefully studied. For the first time, the FeO inner scale on the steel with low Cr and Si contents is observed to incur a eutectoid reaction in a divorced mode during cooling, resulting into a bimodal Ni distribution near the scale/substrate interface. In contrast, a combination reaction of oxygen and FeO layer occurs on the steel with high Cr and Si contents where cracks in scales provide pathway for oxygen transport, and a fine-grained nanocomposite oxide band develops near the interface. Dealloying, partition and segregation during the scale formation are comprehensively addressed. Highlights: Two transform mechanisms are suggested for innermost FeO layer of high-temperature oxide scales of low-alloy steels. Divorced eutectoid reaction occurs on FeO layer due to limited O supply leading to a bimodal Ni distribution near interface. Combination reaction of O2 and FeO layer occurs when cracks in scales provide pathway for O2 transport. Partitioning, dealloying and segregation of solutes at the scales, substrates and interfaces are revealed.